Effect of Nigella Sativa in Improving Blood Glucose Level in T2DM: Systematic Literature Review of Randomized Control Trials - Hoda, Farazul; Khanam, Afifa; Thareja, Mehak; Arshad, Mawrah; Ahtar, Mohd; Najmi, Abul Kalam (Drug Research, 2022)
Background Diabetes mellitus is a highly prevalent condition that affects people of all ages, races, and genders. Medicinal herbs have received a lot of attention from researchers, and they have suggested it to be a good adjuvant to oral diabetes medications because of their combined effects.Objectives The purpose of this systematic review is to summarize the available evidences and literature of Randomized Control Trials (RCTs) on Nigella sativa (NS) in the management of Type 2 Diabetes Mellitus (T2DM).Methods A computerised database search was performed to obtain the relevant clinical trial studies. We searched the following PubMed and Google Scholar databases. Randomized controlled trials (RCTs) comparing NS versus any treatment for the management of T2DM in adults were eligible for inclusion.Results A total of 7 articles were retrieved for interpretation, complete assessment and data extraction in this systematic review. This systematic review seeks to give thorough information on the effects of NS on glucose and insulin profile status in patients with T2DM.Interpretation & Conclusion Different mechanisms are proposed which contribute to the anti-diabetic activity of NS. Various outcome parameters evaluated demonstrate a significant improvement in the management of T2DM and its complications upon intervention with NS.
Keywords: nigella sativa; black cumin; kalonji; thymoquinone; type 2 diabetes mellitus; hypoglycaemia; blood glucose; fasting blood glucose; HbA1c